Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Pada Aplikasi Layanan Top Up Game Codashop - Desfitriady; Pramudya, Ananda Gilang; Rahma, Aditya Noer (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the effect of product quality and price on purchase intention in the Codashop game top-up service application. The research method used is a quantitative method with data collection through questionnaires distributed to Mobile Legends application users who interact via the Twitter/X account @mlbbfess. Data were analyzed using t-tests and F-tests to assess the partial and simultaneous effects between the independent variables (product quality and price) and the dependent variable (purchase intention). The results show that product quality and price have a significant influence on purchase intention. Partially, product quality contributes 85% to purchase intention, while price contributes 43.5%. Simultaneously, product quality and price have a significant effect on purchase intention with an F-value of 52.456, which is greater than the F-table value of 3.09 and significance of 0.000 < 0.05. These findings indicate that improving product quality and setting competitive prices can enhance consumer purchase intentions in the Codashop game top-up service application.